If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8 + -4x + 5 = 5x + 7 + -3x + -10 Reorder the terms: -8 + 5 + 2x + -4x = 5x + 7 + -3x + -10 Combine like terms: -8 + 5 = -3 -3 + 2x + -4x = 5x + 7 + -3x + -10 Combine like terms: 2x + -4x = -2x -3 + -2x = 5x + 7 + -3x + -10 Reorder the terms: -3 + -2x = 7 + -10 + 5x + -3x Combine like terms: 7 + -10 = -3 -3 + -2x = -3 + 5x + -3x Combine like terms: 5x + -3x = 2x -3 + -2x = -3 + 2x Add '3' to each side of the equation. -3 + 3 + -2x = -3 + 3 + 2x Combine like terms: -3 + 3 = 0 0 + -2x = -3 + 3 + 2x -2x = -3 + 3 + 2x Combine like terms: -3 + 3 = 0 -2x = 0 + 2x -2x = 2x Solving -2x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x = 2x + -2x Combine like terms: -2x + -2x = -4x -4x = 2x + -2x Combine like terms: 2x + -2x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| f(x)=x^2-2x+15 | | 9x^2-147x-102= | | 1x+2y(5r)= | | 3x^2-147x-102= | | 8+6p=20 | | 10-p=4 | | 5x-6=12x+62 | | (5x+5)=(3x+5) | | -8x+4=-19x+48 | | 27+53=4x | | (x+8)(x-2)(x+3)(x+2)=0 | | 0.3(2z+7)+2.9=0.5(2z-6) | | 44x^2-30xy+4y^2=0 | | 9x-9=-24x+288 | | -6x+1=10x-47 | | xy-7x=3y | | X+59+70=180 | | 6y-3=19y+62 | | 8+2y-20y-5=0 | | xy=7x+3y | | 1.5=1.4x | | 3.95x^2+0.05x-0.008=0 | | 107-(5x+11)=5(x+6)+x | | -3x=2.2 | | x*9-4=50 | | x^2+(2+m)x+9=0 | | 2y-20y= | | y-7=5(x-12) | | x+.46x=53 | | 5x-5x-1=100 | | (10x-40)+110=180 | | 13p-27=4p-24 |